Tinjauan Penerapan Sistem Informasi Manajemen Puskesmas (Simpus) di UPT Puskesmas Medono Kota Pekalongan Tahun 2023 - Mediati Mediati; Endah Widaningtyas; Roro Kushartanti; M. Nasrul Latif (STIKES HAKLI Semarang, 2025)
The Puskesmas Management Information System (Simpus) is a tool that provides information to support the decision-making process in the implementation of puskesmas management. This study aims to determine the application of Simpus in the Medono Health Center in Pekalongan City based on five management elements, namely man, material, method, money, and machine. This study uses a qualitative descriptive approach with in-depth observation and interview methods, involving five main informants and one source triangulation. The results of the study show that the implementation of Simpus in the registration unit has gone well, but it is not optimal in the PPU poly, dental poly, KIA, and pharmaceutical units. Some of the obstacles found include the unavailability of the Simpus SOPs, limited facilities such as damaged computers at the dental polyclinic, incomplete Simpus application features according to the needs of the unit, and internet network disruptions that cause delays in data input. The conclusion of this study is that the implementation of Simpus at the Medono Health Center has not been optimal. Therefore, it is recommended that the health center provide training to officers related to the use of Simpus and strengthen the management function of the Head of the Puskesmas through periodic monitoring and evaluation so that Simpus can run optimally and support more effective health services.